Review Quality and Reviewer Credibility on Generation Z's Sneaker Purchase Intention in Indonesia: Consumer Trust as a Mediator - Pilari Agemanati Krisnasaputri; Septi Widyasari; Nova Enya Br Maha; Faranita Mustikasari (Politeknik Siber Cerdika Internasional, 2026)
Background: The rapid growth of Indonesia's sneaker market, valued at a projected US736.85 million by 2029, has elevated Generation Z — comprising 27.94% of Indonesia's population — as a critical consumer segment. As digital natives, Generation Z increasingly relies on YouTube-based product reviews to inform purchase decisions, making review quality and reviewer credibility pivotal drivers of consumer trust and purchase intention. Objective: This study examines the influence of review quality and reviewer credibility on Generation Z's sneaker purchase intention in Indonesia, with consumer trust as a mediator within the SOR framework. Methods: A cross-sectional survey of 265 Generation Z respondents who watched sneaker review content on YouTube was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. Results: Review quality has a positive influence on consumer trust and purchase intention, while reviewer credibility emerges as the most dominant stimulus. Consumer trust has been shown to increase purchase intention and partially mediate the relationship between review quality and reviewer credibility with purchase intention, with a stronger mediation effect observed for reviewer credibility. Conclusion: Sneaker industry players need to strengthen digital trust through safe, accurate, and transparent services to encourage Generation Z's purchase intention in the digital shopping ecosystem.